2023
DOI: 10.1017/jfm.2023.468
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cellular bi-stability in the gap between tandem cylinders

Abstract: In the gap region of tandem cylinders, within the reattachment regime, bi-stability is seen to be cellular. Direct numerical simulations at a Reynolds number of 500, and a gap ratio of 3.0, show that shedding of gap vortices occurs in spanwise cells, with lengths between 0.3 and 2.7 cylinder diameters. These unstable vortex cells tend to be asymmetric with respect to the gap centreline, so that vortices are repeatedly shed from just one gap shear layer for several periods. The unstable cells appear within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
7
10
0
Order By: Relevance
“…This is consistent with the results of Aasland et al. (2023), who showed that there are two flow modes in the gap and near wake of straight tandem cylinders at and .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This is consistent with the results of Aasland et al. (2023), who showed that there are two flow modes in the gap and near wake of straight tandem cylinders at and .…”
Section: Resultssupporting
confidence: 93%
“…In accordance with Aasland et al. (2023), the second mode may manifest locally, but in the present case the axial velocity enhances communication along the span, and this may trigger a switch of flow modes at additional spanwise locations. In the supplementary material and movie 2, the mode switch first occurs at , subsequently at and then finally at .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations